1998
DOI: 10.1128/mcb.18.6.3596
|View full text |Cite
|
Sign up to set email alerts
|

p300/CREB Binding Protein-Related Protein p270 Is a Component of Mammalian SWI/SNF Complexes

Abstract: p300 and the closely related CREB binding protein (CBP) are transcriptional adaptors that are present in intracellular complexes with TATA binding protein (TBP) and bind to upstream activators including p53 and nuclear hormone receptors. They have intrinsic and associated histone acetyltransferase activity, suggesting that chromatin modification is an essential part of their role in regulating transcription. Detailed characterization of a panel of antibodies raised against p300/CBP has revealed the existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 55 publications
1
71
0
3
Order By: Relevance
“…Here we report the discovery of ARID1A as a candidate TSG in the T47D breast cancer cell line by using this approach. ARID1A encodes a human homolog of yeast SWI1, which contains a DNA-binding motif (AT-rich interactive domain, ARID) and is an integral member of the hSWI/SNF complex, an ATPdependent, chromatin-remodeling, multiple-subunit enzyme (Takeuchi et al, 1997(Takeuchi et al, , 1998Dallas et al, 1998Dallas et al, , 2000Wang et al, 2004;Wilsker et al, 2004;Patsialou et al, 2005). An increasing body of evidence has demonstrated that SWI/SNF complexes have important roles in gene regulation (Winston and Carlson, 1992;Carlson and Laurent, 1994;Hirschhorn et al, 1995;Kennison, 1995;Sudarsanam et al, 1999Sudarsanam et al, , 2000, cell proliferation (Nagl et al, 2005(Nagl et al, , 2006(Nagl et al, , 2007 and development (Carlson and Laurent, 1994;Kennison, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Here we report the discovery of ARID1A as a candidate TSG in the T47D breast cancer cell line by using this approach. ARID1A encodes a human homolog of yeast SWI1, which contains a DNA-binding motif (AT-rich interactive domain, ARID) and is an integral member of the hSWI/SNF complex, an ATPdependent, chromatin-remodeling, multiple-subunit enzyme (Takeuchi et al, 1997(Takeuchi et al, , 1998Dallas et al, 1998Dallas et al, , 2000Wang et al, 2004;Wilsker et al, 2004;Patsialou et al, 2005). An increasing body of evidence has demonstrated that SWI/SNF complexes have important roles in gene regulation (Winston and Carlson, 1992;Carlson and Laurent, 1994;Hirschhorn et al, 1995;Kennison, 1995;Sudarsanam et al, 1999Sudarsanam et al, , 2000, cell proliferation (Nagl et al, 2005(Nagl et al, , 2006(Nagl et al, , 2007 and development (Carlson and Laurent, 1994;Kennison, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 BRG1-associated factor-155 (BAF155) is occasionally deficient in tumor cell lines, 10 and BAF155-null mouse embryos die at an early implantation stage, indicating the gene is required for normal development although neoplasia in BAF155 heterozygotes has not been examined. 18 Despite this background, there is very little information on expression of SWI/SNF complex components other than hSNF5 in primary human tumor tissue.Human SWI/SNF complex components include a large subunit designated p270 19,20 or BAF-250 21 (HUGO Gene Nomenclature Committee, http://www.gene.ucl.ac.uk/nomenclature/, and the Mouse Genomic Nomenclature Committee, http://www.informatics.jax.org/mgihome/nomen/index.shtml, recommend the official gene designations ARID1A in humans and Arid1a in mice). p270 contains a DNA-binding domain (the ARID) that distinguishes a family of at least 14 human proteins, all of which are implicated in the regulation of differentiation and tumorigenesis.…”
mentioning
confidence: 99%
“…A transformação pelo oncogene ras leva à perda da expressão da proteína mBrm nesta linhagem , já a proteína mBRG (Kwon et al, 1994;Wang et al, 1996bWang et al, e Östlund et al, 1997, tendo um importante papel na liberação de regiões específicas do DNA para transcrição gênica. Este complexo pode apresentar uma composição variada de proteínas (Wang et al, 1996a e b;Dallas et al, 1998e de La Serna et al, 2000, o que está relacionado com uma função transcricional específica (Kadam et al, 2000). Mesmo Brm e BRG são intercambiáveis e a presença de um ou de outro no complexo parece fazer com que este exerça diferentes funções (Aalfs et al, 2001 (Wang et al, 1996a), as quais fazem parte deste complexo multiprotéico.…”
Section: Análise Dos Efeitos Da Superexpressão Do Gene Hbrm Em Célulaunclassified
“…Muitas proteínas, conhecidas por exercerem papéis importantes na regulação do ciclo celular, são capazes de interagir fisicamente com este complexo multiprotéico, ou com suas proteínas componentes. Por exemplo, pode-se citar a proteína p300/CREB (Dallas et al, 1998); GR (Östlund Farrants et al, 1997 e Fryer andArcher, 1998) e pRb ou proteínas da família (Dunaief et al, 1994;Singh et al, 1995;Strober et al, 1996;Trouche et al, 1997Strobeck et al, 2000e Zhang et al, 2000 e c-Myc (Cheng et al, 1999 (Mercado, 1997). Outra hipótese é de que esta proteína poderia corresponder à BAF155 ("BRG/Brm associated factor" 155), proteína de aproximadamente 155 kDa, que faz parte do complexo SWI/SNF em mamífero (Wang et al, 1996a), ou alguma outra proteína que também pode fazer parte ou estar associada ao complexo.…”
Section: Análise Dos Efeitos Da Superexpressão Do Gene Hbrm Em Célulaunclassified
See 1 more Smart Citation